2015
DOI: 10.1002/pbc.25514
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of objective and subjective quality of life among pediatric, adolescent, and young adult bone tumor survivors

Abstract: Background Pediatric, adolescent and young adult (AYA) survivors of bone sarcomas are at risk for poor quality of life (QOL). We conducted a systematic review and meta-analysis to summarize the literature describing QOL in this population and differences in QOL based on local control procedures. Procedure Included studies described ≥5 patients <25 years-old who had completed local control treatment for bone sarcoma, defined QOL as a main outcome, and measured it with a validated instrument. Data extraction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 50 publications
5
42
1
1
Order By: Relevance
“…However, there was no improvement among osteosarcoma survivors, where the biggest change in treatment was replacement of amputation with limb-sparing surgery. Our findings are consistent with literature that indicates a dose-response association (7% (1-13%) per Gray) between CRT dose and risk for adverse events among childhood brain tumor survivors (40), and with meta-analyses that report no difference in long-term disability among childhood sarcoma survivors who require amputation compared to those who had limb-sparing surgery (41). …”
Section: Discussionsupporting
confidence: 91%
“…However, there was no improvement among osteosarcoma survivors, where the biggest change in treatment was replacement of amputation with limb-sparing surgery. Our findings are consistent with literature that indicates a dose-response association (7% (1-13%) per Gray) between CRT dose and risk for adverse events among childhood brain tumor survivors (40), and with meta-analyses that report no difference in long-term disability among childhood sarcoma survivors who require amputation compared to those who had limb-sparing surgery (41). …”
Section: Discussionsupporting
confidence: 91%
“…We also had relatively little racial or ethnic diversity in our sample and could not assess potential cultural differences in HRQOL. Importantly, poor child HRQOL has been associated with other unexamined factors such as socioeconomic status and parent physical and emotional health (23, 40, 44, 47, 58, 59). …”
Section: Discussionmentioning
confidence: 99%
“…Three recent systematic reviews identified a wide array of variables associated with HRQOL in children with cancer (26, 36, 40). Factors consistently associated with poor HRQOL include concurrent cancer therapy (4145), higher treatment-intensity (23, 46, 47), poor prognosis or history of relapse (23, 26), older age (25, 36, 40), cancer-type (where patients with sarcomas or brain tumors have poorer HRQOL) (36, 40, 45, 46), and female sex (23, 25, 40, 44).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found children who underwent either limb sparing or amputation reported no significant differences between either procedures in terms of HRQOL outcomes. 79 Our analysis of HRQOL in children with osteosarcoma found similar results, with no noted differences in HRQOL between children on the two surgical procedures. However, this outcome has been reported to change as children with osteosarcoma progress into survivorship, with evidence suggesting limb-sparing procedures offer higher HRQOL outcomes for survivors of lower-limb osteosarcoma in comparison to survivors with amputations.…”
Section: Aimsupporting
confidence: 72%